The Construction and Realization of the Precise Funding Platform for Impoverished Students in Colleges and Universities Driven by Computer Intelligence Technology - Weiwei Du; Qibo Yu (Advances in Multimedia)
At present, the state’s financial aid for students from financially disadvantaged families is increasing, and the number of students receiving financial aid is also increasing substantially. Poor students have to run back and forth to submit various materials while busy with their own studies, which causes a lot of inconvenience to students and teachers. The development of the poverty-stricken student precision funding platform frees teachers from tedious and low-end work and engages in core affairs, which improves the overall efficiency of school affairs and the controllability of information. In this context, this paper uses computer intelligence technology to realize the construction of the precise funding platform for impoverished students in colleges and universities (CAU) and completes the following tasks: (1) the research status of precise funding for impoverished students in CAU at home and abroad is introduced. (2) The SSI frame structure diagram of the funding information management platform is designed and the specific function description and detailed design of the relevant modules are given. (3) The module function test and system function test of the platform designed in this paper are completed through experiments. The results show that the system is very stable, and the functions are perfectly realized.